A Study of the Disruptive Effect of the Acetate Fraction of Punica granatum Extract on Cryptococcus Biofilms - Villis, Paulo C. M.; de Macedo, Alessandra T.; Furtado, Haryne L. A.; Fontenelle, Pedro H. C.; Gonçalves, Ingrid S.; Mendes, Thayariane L.; Motta, Brenda L. A.; Marinho, Pedro L. L.; Pinheiro, Aruanã J. M. C. R.; Lima-Neto, Lídio G.; Monteiro, Cristina A.; da Silva, Luís C. N.; et al. (Frontiers in Microbiology, 2021)
Cryptococcosis, caused by yeasts of the genus Cryptococcus, is an infectious disease with a worldwide distribution. Cryptococcus neoformans and Cryptococcus gattii are the species that commonly cause this disease in humans; however, infections caused by Cryptococcus laurentii, especially in immunocompromised patients, are increasingly being reported. Owing to the increase in the resistance of fungi to antifungals, and a lack of treatment options, it is important to seek new therapeutic alternatives such as natural products. Among these are plant species such as Punica granatum, which is used in folk medicine to treat various diseases. This study aimed to evaluate the activity of the acetate fraction of P. granatum leaf extract against environmental and clinical isolates of Cryptococcus. Three environmental isolates of C. laurentii, PMN, PMA, and PJL II, isolated from soils of different municipalities in the state of Maranhão, a clinical isolate, C. gattii, from a patient with neurocryptococcosis, and a standard strain of C. gattii (ATCC 32068) were used. The minimum and fractional inhibitory concentrations (MIC and FIC, respectively) and time-kill curve of the extract and fluconazole were determined to assess the susceptibility profile of the fungal isolates. Larvae of Tenebrio molitor were infected with Cryptococcus strains, and the effects of acetate fraction of P. granatum extract and fluconazole on the survival and fungal burden were determined. The extract activity was tested against pre-formed biofilms. The acetate fraction of P. granatum extract showed promising antifungal activity against all the species of Cryptococcus evaluated in this study, with an MIC value lower than that of fluconazole. The indices obtained in the FIC test indicated that the antimicrobial effect of the combination of the extract and antifungal was indifferent for 80% of the isolates. The P. granatum acetate fraction reduced the pre-formed biofilm of some isolates, showing better activity than fluconazole, which is consistent with results from fluorescence microscopy. This is the first study on the use of P. granatum and its ability to inhibit Cryptococcus biofilms; therefore, further studies and tests are needed to investigate the components and mechanism of action of P. granatum against cryptococcosis agents.